Повышение энергетической эффективности процессов обезвоживания пищевого сырья - Бурдо, О. Г.; Безбах, И. В.; Зыков, А. В.; Ахмед, Омар Саид (НТУ "ХПИ", 2008)
Article is devoted questions of creation of thermomechanical units on the basis of rotating thermosiphons (RTS). The analysis of technologies of thermal processing, concentrating liquid products, drying of disperse materials is made. Problems are revealed and decision ways are defined. Classification of thermomechanial units is resulted. Application of devices with RTS for various foodstuffs is considered. Results of experimental modeling of heat–mass exchange in devices with RTS are resulted. Calculation and the analysis of efficiency of application of the device in technological lines are made. Prospects of designs of independent thermo-mechanical units, their functional problems and the advantages, expected effect are considered
Keywords: пищевая промышленность; термомеханические аппараты; термосифоны; термообработка; выпаривание; сушка